What have we learned from a case of convalescent plasma treatment in a two-time kidney transplant recipient COVID-19 patient? A case report from the perspective of viral load evolution and immune response - Aldunate, Fabian; Fajardo, Alvaro; Ibañez, Natalia; Rammauro, Florencia; Daghero, Hellen; Arce, Rodrigo; Ferla, Diego; Pereira-Gomez, Marianoel; Salazar, Cecilia; Iraola, Gregorio; Pritsch, Otto; Hurtado, Javier; et al. (Frontiers in Nephrology, 2023)
Coronavirus disease 2019 (COVID-19), an infectious disease caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus, can have a wide range of clinical manifestations, ranging from asymptomatic disease to potentially life-threatening complications. Convalescent plasma therapy has been proposed as an effective alternative for the treatment of severe cases. The aim of this study was to follow a two-time renal transplant patient with severe COVID-19 treated with convalescent plasma over time from an immunologic and virologic perspective. A 42-year-old female patient, who was a two-time kidney transplant recipient, was hospitalized with COVID-19. Due to worsening respiratory symptoms, she was admitted to the intensive care unit, where she received two doses of convalescent plasma. We analyzed the dynamics of viral load in nasopharyngeal swab, saliva, and tracheal aspirate samples, before and after convalescent plasma transfusion. The levels of pro-inflammatory cytokines and antibody titers were also measured in serum samples. A significant decrease in viral load was observed after treatment in the saliva and nasopharyngeal swab samples, and a slight decrease was observed in tracheal aspirate samples. In addition, we found evidence of an increase in antibody titers after transfusion, accompanied by a decrease in the levels of several cytokines responsible for cytokine storm.